Adequação da distribuição de água no solo para fruteiras tropicais microirrigadas - Alves, Josualdo Justino (1996)
A field study was done at Paraipaba - Ce, Brazil, in a sandy soil, to determine surface and subsurface water distribution from two emmiters, a microsprayer (MS 7200) and a microsprinkler (MA 2001) and to evaluate microirrigation in an area planted with "graviola" (Annona muricata L.). Each emmiter was run for 1,5; 3,0 and 4,5 hours, replicated three times, and the water collected by cans at the soil surface. Twenty four hours after the water applications, soil samples were taken in a trench, soil moisture determined, and traced equal moisture curves and wet bulb profiles. Surface water distribution patterns were evaluated trough the uniformity coefficients CU, DU and CV, according to the methodology proposed by Christiansen (1942) and Merriam and Keller (1978), considering alI tha collecting cans on the grid arround the emmiters and only the cans that received water. For both emmiters and collecting schemes, the coefficients CU and DU had low values and very high CV, indicating a poor surface distribution of water. Subsurface distribution of water had a much better uniformity, as compared to the surface. The microirrigation system at the "graviola" area was evaluated by the methodology proposed by Merriam, Keller and Alfaro (1973) for the uniformity of application (CU) and Merriam and Keller (1978) for the potential efficiency of the application (PELQ). The CU and PELQ values were 89.1% and 80.2%, indicating a good performance for the system.